The Culture of Rape is Debated: The Discord of Feelings between Journalism and Diário Gaúcho Readers - Stocker, Pâmela Caroline; Dalmaso, Silvana Copetti (Brazilian journalism research, 2018)
From the understanding of journalism as a discursive gender (Benetti, 2008) which contributes towards maintaining consensual values in society (Hall et al, 1993), this article analyzes the discourse of readers on news stories from the Diário Gaúcho newspaper, published on the internet in June, 2016, addressing assaults on women in the city. Using post-structuralist feminist studies and the Discourse Analysis (DA) as theoretical support, 201 comments were examined, identifying four nuclei meanings: blaming the victim, naturalizing assault/instinct, relativizing assault and disqualifying journalism. These meanings were evidence of the discourse from these readers going towards crystallizing historical-cultural constructions on gender and social roles of men and women, justifying and emphasizing the importance of journalistic approaches that break from traditional cultural maps of meaning. A partir do entendimento do jornalismo como gênero discursivo (Benetti, 2008) que contribui para manter os valores consensuais da sociedade (Hall et al., 1993), este artigo analisa o discurso dos leitores sobre a reportagem do jornal Diário Gaúcho, publicada na internet em junho de 2016, que aborda o assédio urbano a mulheres. Com aporte teórico dos estudos feministas pós-estruturalistas e por meio da Análise de Discurso (AD), foram examinados 201 comentários e identificados quatro núcleos de sentido: culpabilização da vítima, naturalização do assédio/ instinto, relativização do assédio e desqualificação do jornalismo. Tais sentidos mostraram que o discurso desses leitores opera para a cristalização das construções histórico-culturais sobre gênero e papeis sociais reservados ao feminino e ao masculino, o que justifica e ressalta a importância de abordagens jornalísticas que rompam com os tradicionais mapas culturais de significado. A partir de la compresión del periodismo como género discursivo (Benetti, 2008) que contribuye a mantener los valores consensuados de la sociedad (Hall et al., 1993), este artículo analiza el discurso de los lectores sobre el reportaje del periódico Diário Gaúcho, publicado en internet en Junio de 2016, que aborda el acoso urbano a las mujeres. Con aporte teórico de los estudios feministas post-estructuralistas y por medio del Análisis de Discurso (AD), se examinaron 201 comentarios y cuatro núcleos de sentido se identificaron: culpabilización de la víctima, naturalización del acoso / instinto, relativización del acoso y descalificación del periodismo. Tales sentidos mostraron que el discurso de estos lectores opera para la cristalización de las construcciones histórico-culturales sobre género y papeles sociales reservados al femenino y al masculino, lo que justifica y resalta la importancia de enfoques periodísticos que rompan con los tradicionales mapas culturales de significado.